Semantic Characteristics of the English and Uzbek Languages - Nilufar Zubaydova (International Journal on Integrated Education, 2022)
At this stage in the development of linguistics, the study of linguistic units, including proverbs, is of particular importance. This study is devoted to the study of the systematic semantics of English and Uzbek proverbs. The problem's criticality one of the problems that has been actively developing in linguistics in recent years is determining the linguistic status of complex language forms that exceed the volume of non-predicative expressions. Proverbs representing one of these types of formation are traditionally studied within the context of phraseology, resulting in the researcher's natural desire to describe the material through an already known prism-linguistic units.